2023
DOI: 10.1111/jfd.13818
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antibacterial activity of medicinal plant Sophora flavescens against Streptococcus agalactiae infection

Abstract: Streptococcosis disease caused by Streptococcus agalactiae (Group B Streptococcus, GBS) results in a huge economic loss of tilapia culture. It is urgent to find new antimicrobial agents against streptococcosis. In this study, 20 medicinal plants were evaluated in vitro and in vivo to obtain medicinal plants and potential bioactive compounds against GBS infection. The results showed that the ethanol extracts of 20 medicinal plants had low or no antibacterial properties in vitro, with a minimal inhibitory concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Oxymatrine (OMT), an active monomer extracted from various TCMs including Sophora avescens Ait and Radix Sophorae Tonkinensis (Bi et al, 2012, Liang et al, 2023, has demonstrated e cacy in managing chronic hepatitis B (Lu et al, 2004). Besides its hepatoprotective role, OMT exhibits potential against tumorigenesis, in ammation, and bacterial infections (Li et al, 2022, Cao et al, 2023, Zhang et al, 2023a. Notably, in Hepatitis B virus (HBV) transgenic mice liver (Chen et al, 2001), OMT reduces levels of HBsAg and HBcAg, and as a potent immunosuppressant, it curtails replication and in ammation of type A in uenza virus via the TLR4, p38 MAPK, and NF-κB pathways (Dai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oxymatrine (OMT), an active monomer extracted from various TCMs including Sophora avescens Ait and Radix Sophorae Tonkinensis (Bi et al, 2012, Liang et al, 2023, has demonstrated e cacy in managing chronic hepatitis B (Lu et al, 2004). Besides its hepatoprotective role, OMT exhibits potential against tumorigenesis, in ammation, and bacterial infections (Li et al, 2022, Cao et al, 2023, Zhang et al, 2023a. Notably, in Hepatitis B virus (HBV) transgenic mice liver (Chen et al, 2001), OMT reduces levels of HBsAg and HBcAg, and as a potent immunosuppressant, it curtails replication and in ammation of type A in uenza virus via the TLR4, p38 MAPK, and NF-κB pathways (Dai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) offers a distinct perspective on antiviral therapy, emphasizing treatments that are less likely to induce drug resistance. Oxymatrine (OMT), a quinolizidine alkaloid extracted from the roots of Sophora flavescens Aiton and Sophora tonkinensis Gagnep (Fabaceae) [16,17], exhibits a broad spectrum of biological activities [18], including hepatoprotection, anti-tumorigenesis, anti-inflammation, and antibacterial effects [19][20][21]. Its capacity to modulate the immune response and inhibit viral replication of hepatitis B virus (HBV) in transgenic mice underscores its potential as an immunomodulatory agent [22].…”
Section: Introductionmentioning
confidence: 99%